E-Government Icore: Meningkatkan Pelayanan Publik Berbasis Aplikasi Di Kabupaten Pangkep - Malik, Ihyani (Universitas Muhammadiyah Mataram, 2024)
The purpose of this study is to ascertain how the Department of Population and Civil Registration in the Pangkep district has improved public services through the use of e-government core. Qualitative research using a descriptive research design is the method employed. Techniques for gathering data include documentation, interviews, and observation. The study's findings include 1) Components of Support, Since the icore application's formal introduction, the government is stated to have offered excellent support for the development of e-government implementation, and this support has only increased. 2) Components of capability, The Pangkep Regency Population and Civil Registration Office's capacity to implement e-government core and improve public services has been deemed ideal in terms of financial, infrastructural, and human resources. This is derived from the APBD and has to do with the accessibility of financial or budgetary resources. 3) Valuable Components (advantages) Because of the many conveniences provided, the community has experienced the value or benefits of the icore application.